Electronic spectra, ESR and crystal structure of tetrahedral halocuprates(II). The existence of cations (2tbpo·H+) with a very short hydrogen bond - Massabni, Antonio Carlos [UNESP]; Nascimento, Otaciro Rangel; De Almeida Santos, Regina Helena; Porto Francisco, Regina Helena; Lechat, Johannes Rüdiger (Elsevier, 1983)
Two compounds [2tbpo·H+)2[CuCl4]= (yellow) and (2tbpo·H+)2[CuBr4]= (dark purple) (tbpo = tribenzylphosphine oxide) have been prepared and investigated by means of crystal structure, electronic, vibrational and ESR spectra. The crystal structure of the (2tbpo·H+)2[CuCl4]= complex was determined by three-dimensional X-ray diffraction. The compound crystallizes in the space group P42/n with unit-cell dimensions a = 19.585(2), c = 9.883(1)Å, V = 3790 (1)Å3, Z = 2, Dm = 1.303 (flotation) Dx = 1.302 Mg m-3. The structure was solved by direct methods and refined by blocked full-matrix least-squares to R = 0.053 for 2583 observed reflections. Cu(II) is coordinated to four chlorides in a tetrahedral arrangement. Tribenzylphosphine oxide molecules, related by a centre of inversion, are connected by a short hydrogen bridge. Chemical analysis, electronic and vibrational spectra showed that the bromide compound is similar to the chloride one and can be formulated as (2tbpo·H+)2[CuBr4]=. The position of the dd transition bands, the charge transfer bands, the ESR and the vibrational spectra of both complexes are discussed. The results are compared with analogous complexes cited in the literature. © 1983.